Partitioning Pervasive Detrital Geochronologic Age Distributions in the Southern Alaskan Forearc - Finzel, Emily S. (Frontiers in Earth Science, 2019)
The extensive detrital zircon U-Pb geochronologic dataset presented here includes new and compiled data (N=38; n=8,006) from modern rivers that together comprehensively characterizes the geographic distribution of pervasive Mesozoic—Cenozoic igneous belts across mountainous regions in south-central Alaska, including the northern Chugach Mountains, Talkeetna Mountains, and western, central, and eastern Alaska Range. These data are compared to an extensive detrital zircon U-Pb dataset from Lower Cretaceous to Pliocene strata in the forearc basin (N=29; n=8,678) using a recently developed unmixing approach to investigate the variations in long-term provenance and sediment dispersal patterns in the basin in response to tectonic events. During the Early Cretaceous, the primary sediment source was an exhumed Jurassic arc located north of the basin, but new sediment derived from accretionary prism strata in the northern Chugach Mountains during the Late Cretaceous coincides with final suturing of the Insular terranes with North America and a change in plate kinematics. Eocene strata record major sediment derivation from the western Alaska Range after passage of a subducting spreading ridge. By the Oligocene, shallow subduction of the Yakutat microplate triggered a rejuvenation of exhumation in the northern Chugach Mountains that continued through the Early-Middle Miocene. And overall inboard shift of dominant source regions to the Talkeetna Mountains and central Alaska Range likely reflects the continued insertion of the shallow slab beneath south-central Alaska. The integrated approach of strategic modern river sampling and comprehensive basin strata characterization in conjunction with an inverse Monte Carlo approach of mixture modeling demonstrates a useful approach for partitioning of widespread and pervasive ages in sediment source terranes.